365 Effects of coated-cysteamine on growth performance, carcass characteristics, meat quality and lipid metabolism in finishing pigs. (7th December 2018) - Tao, W; Wang, M; Li, H; Yu, R; Li, Z
Abstract: This study was conducted to evaluate the effects of coated-cysteamine (CS) on growth performance, carcass characteristics, meat quality and lipid metabolism in finishing pigs. A total of 160 finishing pigs (60.1 ± 1.01 kg BW) were randomly divided into four groups, with 4 pens per group and 10 pigs (5 gilts and 5 barrows) per pen. Pigs were fed a basal diet supplemented with 0, 100, 200, or 400 mg/ kg CS, corresponding to 0, 27, 54, or 108 mg/ kg cysteamine, respectively. All pigs were given free access to feed and water for forty days. After the feeding trial, eight pigs were selected from each treatment and slaughtered to measure carcass and meat quality, and to collect serum samples for laboratory analysis. Results showed that supplemental 100 mg/kg CS increased ADFI (3.03%, P < 0.05), while 200 mg/kg and 400 mg/kg CS decreased ADFI (1.52%, 3.03%, respectively; P < 0.05). Supplemental CS increased carcass lean ratio (2.26%, 2.38%, 6.13%, respectively; P < 0.05). The 24 h drip loss was decreased by 17.51% (P < 0.05) and 12.03% (P < 0.05) respectively in the 100 and 200 mg/kg CS groups, and Hunter b was reduced by 14.49% (P < 0.05) in the 200 mg/kg CS group. Serum free fatty acids of CS supplementation group was higher (22.78%, 32.45%, 41.35%, respectively; P < 0.05) than that in control group. Dietary supplementation of CS decreased activities of fatty acid synthase (16.26%, 15.43%, 14.44%, respectively; P < 0.05), while increased the activity of hormone-sensitive lipase (64.82%, 41.95%, 106.33%, respectively; P < 0.05) and isocitrate dehydrogenase (44.09%, 33.76 %, 70.21%, respectively; P < 0.05) in subcutaneous adipose tissue. These results suggested that dietary supplementation of coated-cysteamine has beneficial effects on carcass characteristics and meat quality, and positively affected lipid catabolism in finishing pigs.